Gadolinium(III)-based porous luminescent metal-organic frameworks for bimodal imaging - Kundu, Tanay; Mitra, Shouvik; Diaz Diaz, David; Banerjee, Rahul (Chempluschem, 2016)
Gd-III-based metal-organic frameworks, Gd-pDBI-1 and Gd-pDBI-2, have been synthesized using the linker pDBI (pDBI=1,4-bis(5-carboxy-1H-benzimidazole-2yl)benzene). They exhibited structural diversity due to subtle change in reaction constituents. Owing to the judicious choice of the fluorescent linker, the materials could be used for bimodal imaging (fluorescent and magnetic resonance) and displayed a modest T1 relaxivity value.